Effects of Stability Ball Core Exercises on Gluteus Maximus, Hamstring, Gastrocnemius, and Soleus Muscle Strength Among Post-Stroke Patients - Annisa Nuraini; Erni Buston; Efrizon Efrizon (MEDICA (International Medical Scientific Journal), 2026)
Indonesia is the first rank of people with stroke in Asia and contribute 4.62% of all causes of mortality. It was predicted that in 2030, the number will increase to 23.3 million mortalities due to stroke. In Indonesia, in 2021, 12 people out of 1000 were diagnosed with stroke. Most of these conditions resulted in muscle weaknesses, especially in the lower extremities. This condition is a barrier to daily activities related to physical movement. The aim of this study is to test the effect of stability ball core exercises on gluteus maximus, hamstring, gastrocnemius, and soleus muscle strength among post-stroke patients. This study is a quasi-experiment pre and post-test with intervention and control groups. The sample size in this study consisted of 20 patients for each group selected by purposive sampling. The Mann-Whitney statistical test analyzed the data. The result found that stability ball core exercise significantly improved the muscle strength of the Gluteus Maximus and Hamstring, but found no significance with the gastrocnemius and soleus muscles. The future study could add a follow-up study to evaluate the long-term impact of this treatment.